Utilizing gravity surveys for subsurface feature identification in foundation planning - Nordiana Mohd Muztaza,; Thanath Gopalan,; Nur Amanina Mazlan,; Jamaludin Othman,; Nazrin Rahman,; Najmiah Rosli,; Rosli Saad,; Farid Najmi Rosli,; Athirah Rosli,; Bashir, Yasir (Penerbit Universiti Kebangsaan Malaysia, 2025)
Understanding the distribution and extent of solution features such as cavities and pinnacles in limestone bedrock is crucial for anticipating potential challenges and planning appropriate foundation solutions. This study employed microgravity surveying to complement available borehole data and map karst features, particularly cavities, within the limestone bedrock. The survey was conducted on a 5 m × 5 m grid interval, establishing a total of 91 stations. Reduced Bouguer and residual anomalies were contoured and plotted using the GEOSOFT Oasis Montaj Mapping system. Anomalies of interest were further analyzed through 2-D gravity modeling using PotentQ software to determine the dimensions of the causative bodies. The survey results, presented as Bouguer, residual, and Bouguer anomaly horizontal gradient maps, showed a small range of gravity values (-9.24 to -9.10 mGal), indicating minimal variation in limestone bedrock topography. Gravity highs were associated with shallow limestone bedrock, while isolated gravity lows suggested the presence of cavities. Horizontal gradient maps highlighted peaks corresponding to the edges of these cavities and potential channel-like features. Borehole data corroborated the microgravity findings, with bedrock encountered at depths between 9.6 m and 12.3 m indicating deeper bedrock towards the south. The 2-D gravity modeling suggested a sediment-filled cavity approximately 7 m thick and 15 m wide in an east-west orientation, aligning well with borehole data. The combined use of borehole data and microgravity surveying proved effective in characterizing subsurface karst features, providing valuable insights for foundation planning leading to safer and more efficient construction practices.